The biotransformation of phenolic pollutants using polyphenol oxidase - Boshoff, Aileen (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2002)
The potential of using mushroom polyphenol oxidase (EC 1.14.18.1) as a biocatalyst for the biotransformation of phenols to produce catechols in an aqueous medium was investigated. Polyphenol oxidase is characterised by two distinct reactions i.e., the ortho-hydroxylation of phenols to catechols (cresolase activity) and the subsequent oxidation of catechols to orthoquinones (catecholase activity). In order to facilitate the development of a process to produce catechols, the accumulation of catechol as a true intermediate product released in the reaction system needed to be investigated, as its release had been disputed due to the oxidation of catechols to o-quinones. Using LC-MS, catechol products were successfully identified as true intermediate products formed during biocatalytic reactions in water.
Keywords: Polyphenol oxidase; Sewage -- Purification